2018
DOI: 10.1021/acs.energyfuels.8b02031
|View full text |Cite
|
Sign up to set email alerts
|

Lean Flammability Limits of Syngas/Air Mixtures at Elevated Temperatures and Pressures

Abstract: New experimental results for lean flammability limits (LFLs) of syngas/air (H2/CO/air) mixtures have been obtained at temperatures up to 200 °C and pressures up to 9 bar. ASTM Standard E918 (1983) provided the framework for tests at these elevated conditions, using a 1-L pressure-rated test cylinder in which the fuel–air mixtures were prepared and then ignited. The purpose for characterizing the flammability limits for these gaseous mixtures is to facilitate development of appropriate procedures for the safe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this table, the emphasis is on experimental work in which the FLs were determined with vessels of different volumes and/or geometries. As observed in Figure , there are 73 works in which cylindrical vessels were used, ,,,,,, 62 works in which spherical vessels were used, ,,,, ...…”
Section: Experimental Determination Of the Flammability Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this table, the emphasis is on experimental work in which the FLs were determined with vessels of different volumes and/or geometries. As observed in Figure , there are 73 works in which cylindrical vessels were used, ,,,,,, 62 works in which spherical vessels were used, ,,,, ...…”
Section: Experimental Determination Of the Flammability Limitsmentioning
confidence: 99%
“…General characteristics of most common experimental equipment used to determine the flammability limits. (a) Experimental works with cylindrical vessels. ,,,,,, (b) Experimental works with spherical vessels. ,,,, …”
Section: Experimental Determination Of the Flammability Limitsmentioning
confidence: 99%
“…The flammability limits of hydrogen, ,, hydrogen/hydrocarbons, hydrogen/carbon monoxide, ,,,,, and hydrogen/carbon monoxide/methane mixtures have been studied experimentally at high temperatures and pressures. In contrast to hydrogen and its mixtures, the flammability limit of ammonia has rarely been studied.…”
Section: Advances In the Experimental Study Of The Flammability Limit...mentioning
confidence: 99%
“…They found similar results to previous studies, showing an increase in the flammable range (increase in UFL; the LFL decreases as the initial test pressure increases). However, Jaimes et al , found that the lower flammability limits of each mixture ratio of hydrogen/carbon monoxide gradually increased with the initial pressure because the initial pressure had an important influence on the elongation rate of the flame. The initial pressure affects the elongation rate of the flame and then affects the propagation form of the flame.…”
Section: Advances In the Experimental Study Of The Flammability Limit...mentioning
confidence: 99%
“…This method can not only recycle the exhaust heat, but also enable the engine to be closer to the constant volume cycle, and, thus, the thermal efficiency of the engine is improved (Ji et al, 2013). In addition, dissociated methanol gas is rich in hydrogen, and mixing hydrogen with a hydrocarbon fuel for combustion can increase the flame speed (Zhao et al, 2019), and extend the lean-burn limit (Jaimes et al, 2018). Lean combustion enables the fuel to burn completely, which further increases the thermal efficiency, and may reduce the emissions of CO (Liu and Dumitrescu, 2019).…”
Section: Introductionmentioning
confidence: 99%